The role of local government policy in enhancing zakat revenue: A case study of BAZNAS in Serang Regency - Husain, Muhammad Kamil; Maulana, Delly; Syihabudin, Syihabudin; Adawiah, Amalia Muazzah; Wasehudin, Wasehudin (International Journal of Nusantara Islam, 2025)
This study examines how local government policy contributes to the effectiveness of zakat revenue collection, focusing on the case of BAZNAS in Serang Regency, Indonesia. Zakat, an Islamic fiscal obligation, serves not only as an act of worship but also as a mechanism for socio-economic redistribution. Despite its potential, zakat collection in many regions remains suboptimal due to fragmented policies and weak institutional synergy. This research addresses a critical gap in global Islamic finance literature by investigating zakat governance at the subnational level, especially in a decentralized administrative context. Using a qualitative method that includes document analysis and semi-structured interviews with key stakeholders, the study explores how formal regulations, government facilitation, and inter-agency coordination shape institutional performance. The findings reveal that local policies—such as mandatory zakat deductions for civil servants, operational support, and integration of zakat into regional development planning—significantly enhance zakat income and institutional legitimacy. However, challenges such as limited bureaucratic capacity, inconsistent implementation, and fragmented institutional roles hinder optimal performance. The study concludes that effective zakat governance requires not only normative alignment with Islamic values but also robust policy design, administrative professionalism, and participatory mechanisms. By bridging institutional theory and Islamic public finance, this study offers a contextualized model of state–faith institutional synergy that may be applied to other Muslim-majority countries or regions with similar governance dynamics.